Selective versus standard cerebro‐myocardial perfusion in neonates undergoing aortic arch repair: A multi‐center study. Issue 8 (22nd February 2019) - Luciani, Giovanni Battista; Hoxha, Stiljan; Angeli, Emanuela; Petridis, Francesco; Careddu, Lucio; Rungatscher, Alessio; Caputo, Massimo; Gargiulo, Gaetano
Abstract: The results of neonatal aortic arch surgery using cerebro‐myocardial perfusion were analyzed. Selective cerebral and myocardial perfusion, using two separate pump rotors, was compared with standard perfusion, using a single pump rotor with an arterial line Y‐connector. Between May 2008 and May 2016, 69 consecutive neonates underwent arch repair using either selective cerebro‐myocardial perfusion (Group A, n  = 34) or standard perfusion (Group B, n  = 35). The groups were similar for age, weight, BSA, prevalence of one‐stage or staged repair, and single ventricle palliation; male gender was more frequent in Group A. The duration of the cerebro‐myocardial perfusion was comparable (27 ± 8 vs. 28 ± 7 min, P  = 0.9), with higher flows in Group A (57 ± 27 vs. 39 ± 19 mL/kg/min, P  = 0.01). Although cardioplegic arrest was more common in Group B (13/34 vs. 23/35, P  = 0.03), the duration of myocardial ischemia was longer in Group A (64 ± 41 vs. 44 ± 14 min, P  = 0.04). There was 1 hospital death in each group, with no permanent neurological injury in either group. Cardiac morbidity (1/34 vs. 7/35, P  = 0.02) was more common in Group B, while extracardiac morbidity was similar in both the groups. During follow‐up (3.2 ± 2.4 years), 5 late deaths occurred with a comparable 5‐year survival rate (75 ± 17% vs. 88 ± 6%, P  = 0.7) and freedom from arch reintervention (86 ± 6% vs. 84 ± 7%, P  = 0.6). Risk of cardiac morbidity was greater with standard cerebro‐myocardial perfusion (OR = 5.2, CI 3.3–6.8, P  = 0.001) and with perfusion flows less than 50 mL/kg/min (OR 3.7, CI 1.87–5.95, P  = 0.04). Cerebro‐myocardial perfusion is a safe and effective strategy to protect the brain and heart in neonates undergoing arch repair. Selective techniques using higher perfusion flows may further attenuate cardiac morbidity.